Предмет: Алгебра,
автор: miwa2307
Спрости вираз
(4a³+a+3) (a-1)
(2a+3b)²
(a-b) (a+b) (a-3b)
6xy+3(x-y)²
Ответы
Автор ответа:
0
Ответ:
(4a^3+a+3)(a-1)=4a^3*(a-1)+a*(a-1)+3(a-1)=4a^4-4a^3+a^2-a+3a-3=4a^4-4a^3+a^2+2a-3
(2a+3b)^2=(2a)^2+2*2a*3b+(3b)^2=4a^2+12ab+9b^2
(a-b) (a+b) (a-3b) =(a^2-b^2)*(a-3b)=a^3-3a^2b-ab^2+3b^3
6xy+3(x-y)²=3(2xy+(x-y^2))=3(2xy+x^2-2xy+y^2)=3(x^2+y^2)
Объяснение:
Похожие вопросы
Предмет: География,
автор: катюшка124
Предмет: Русский язык,
автор: valezhnikova04
Предмет: Русский язык,
автор: dianabozhanova21
Предмет: Математика,
автор: Mika111111111111
Предмет: Математика,
автор: Vladik6kl